Strategy of robotic surgeons to exert public influence through Twitter. Issue 1 (23rd February 2016) - Borgmann, Hendrik; Woelm, Jan; Nelson, Karen; Gust, Kilian; Mager, Rene; Reiter, Michael; Schilling, David; Bartsch, Georg; Blaheta, Roman; Haferkamp, Axel; Tsaur, Igor
Abstract: Background: Twitter is gaining growing popularity as a communication platform and potential tool to influence the public in medical matters. The aim here is to examine whether and how robotic surgeons use Twitter more influentially than other urologists. Methods: Robotic surgeons and other urologists that tweeted at the European urology congress were compared by assessing Twitter Follower/Following Ratio, Retweet Rank and Percentile and their Twitter strategies. Results: Robotic surgeons had a significantly higher Twitter Follower/Following Ratio (2.1, 1.4–2.4) and Retweet Rank percentile (92.1%, 90.5–93%) than other urologists (1.2, 0.8–2.1 and 88.9%, 87.3–91.7%, respectively). Robotic surgeons used original tweet content and links more often than other urologists (69.4% vs 53.8%, and 19.8% vs 12.5%, respectively). Conclusions: Robotic surgeons had a higher public influence on Twitter than other urologists and posted original tweets and links in tweets and profiles more frequently. This strategy might optimize Twitter use by healthcare professionals in the future. Copyright © 2016 John Wiley & Sons, Ltd.